Studi Kasus : Mengoptimalkan Potensi Anak Low Vision melalui Pendidikan Inklusi - Irawan, Clairina Verminthia Dheanova; Bassalamah, Nadila Salma; Maulidia, Nuhla; Afriani, Iin; Anjani, Asila Sekar; Ummah, Umi Safiul; Harisandi, I GST. Ngurah Putu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Children with low vision are part of the special needs group who still retain limited visual abilities that can be maximized with proper support. This study explores the importance of adapting teaching media, instructional methods, and inclusive school environments for low vision children, focusing on a case study at SD Negeri Purwantoro 7, Malang City. The findings reveal that concrete learning media and inclusive social interactions play a vital role in boosting the motivation and understanding of low vision students. Support from teachers, peers, and the broader community is essential for creating equitable and meaningful education.